Implementasi Sistem Klasifikasi Untuk Seleksi Pemenang Tender Dengan Metode ANN (Artificial Neural Network) - Axel Donielson Gaing; Fajar Septian (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Tender is a series of bidding activities that aim to select, obtain, determine and show which company is the most appropriate and appropriate to work on a work package. The tender is divided into several parts. In the Selection of Tender Participants, it is carried out through Evaluation stages such as Administration, Technical, Price, Qualification and Final Value. The problem is that in carrying out the classification for this selection requires a system that can classify bidders who pass the selection and those who do not pass the tender selection, and the results of its implementation. The method currently used is still ineffective because it is prone to human error, such as inputting the results of recaps from each selection stage into the final evaluation result which causes differences in the results, and difficulties in classifying participants who pass the selection and do not pass the tender selection. To overcome this problem, the authors developed a classification system for tender selection using the Artificial Neural Network method which relies on neurons to carry out classification so that it can select participants who pass the tender and do not pass the tender. From the test results, the accuracy levels for Data Training and Data Testing were 99.15% and 98.04% and the evaluation results from the Accuracy metrics were 97.20%, Precision, Recall and F1-Score were 97.00%